The contribution of pharmaceutically active compounds from healthcare facilities to a receiving sewage treatment plant in Canada. (22nd October 2015) - Kleywegt, Sonya; Pileggi, Vince; Lam, Yuet Ming; Elises, Alan; Puddicomb, Aaron; Purba, Gurminder; Di Caro, Joanne; Fletcher, Tim
Abstract: Concentrations and percent loadings of pharmaceutically active compounds (PhACs) and other emerging contaminants released from healthcare facilities (2 hospitals and a long‐term care facility) to a sewage treatment plant (STP) in a large urban sewershed were evaluated. An additional hospital outside the sewershed was also monitored. Fourteen of the 24 steroids/hormones and 88 of the 117 PhACs and emerging contaminants were detected at least once. Commonly used substances, including cotinine, caffeine and its metabolite 1, 7‐dimethylxanthine, ibuprofen and naproxen (analgesics), venlafaxine (antidepressant), and N, N ‐diethyl‐meta‐toluamide (insect repellant), were detected in all samples at all sites. Concentrations detected in the large specialty hospital outside the sewershed were similar to those within the sewershed. Cytotoxic drugs (tamoxifen and cyclophosphamide) and x‐ray contrast media (iopamidol and diatrizoic acid) were infrequently detected in hospital effluents. Analysis for antibiotics indicated that azithromycin, clarithromycin, ciprofloxacin, erythromycin, ofloxacin, and sulfamethoxazole were consistently detected in hospital wastewaters, as was triclosan (antibacterial agent). Fifteen compounds individually contributed greater than 1% to the total PhAC and emerging contaminant load to the STP from the 2 hospitals in the sewershed, and 9 compounds in the STP effluent exceeded ecotoxicological criteria. The present survey demonstrates that point source discharges from healthcare facilities in this sewershed make a small contribution to the overall PhAC and emerging contaminant loading compared with the total concentrations entering the receiving STP. Environ Toxicol Chem 2016;35:850–862. © 2015 SETAC